A narrow window of summer temperatures associated with shrub growth in Arctic Alaska. (8th October 2020) - Andreu-Hayles, Laia; Gaglioti, Benjamin V; Berner, Logan T; Levesque, Mathieu; Anchukaitis, Kevin J; Goetz, Scott J; D'Arrigo, Rosanne
Abstract: Warming in recent decades has triggered shrub expansion in Arctic and alpine tundra, which is transforming these temperature-limited ecosystems and altering carbon and nutrient cycles, fire regimes, permafrost stability, land-surface climate-feedbacks, and wildlife habitat. Where and when Arctic shrub expansion happens in the future will depend in part on how different shrub communities respond to warming air temperatures. Here, we analyze a shrub ring-width network of 18 sites consisting of Salix spp. and Alnus viridis growing across the North Slope of Alaska (68–71° N; 164–149° W) to assess shrub temperature sensitivity and compare radial growth patterns with satellite NDVI (normalized difference vegetation index) data since 1982. Regardless of site conditions and taxa, all shrubs shared a common year-to-year growth variability and had a positive response to daily maximum air temperatures (Tmax) from ca. May 31 (i.e. Tmax ∼6 ° C) to early July (i.e. Tmax ∼12 ° C), two-thirds of which were significant correlations. Thus, the month of June had the highest shrub growth-temperature sensitivity. This period coincides with the seasonal increase in temperature and phenological green up on the North Slope indicated by both field observations and the seasonal cycle of NDVI (a proxy of photosynthetic activity). Nearly all of the sampled shrubs (98%) initiated their growth after 1960, with 74% initiated since 1980. This post-1980 shrub-recruitment pulse coincided with ∼2 °C warmer June temperatures compared to prior periods, as well as with positive trends in shrub basal area increments and peak summer NDVI. Significant correlations between shrub growth and peak summer NDVI indicate these radial growth patterns in shrubs reflect tundra productivity at a broader scale and that tundra vegetation on the North Slope of Alaska underwent a greening trend between 1980 and 2012.